2022
DOI: 10.3390/su14052945
|View full text |Cite
|
Sign up to set email alerts
|

Public Transport COVID-19-Safe: New Barriers and Policies to Implement Effective Countermeasures under User’s Safety Perspective

Abstract: The COVID-19 emergency forced cities worldwide to adopt measures to restrict travel and implement new urban public transport solutions. The discontinuity and reduction of services made users recognize public transport systems as contamination vectors, and the decrease in the number of passengers can already be seen in several places. Thus, this study assessed the impact of the COVID-19 pandemic on urban public transport. We used hybrid choice models (HCMs) to identify the new barriers and potential solutions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…The choice of travelling by PT during the COVID-19 pandemic is dependent on either the impossibility of using other travel modes, due to economic, social, and housing limitations, or the satisfaction from the quality of delivered services ( Lucchesi et al, 2022 ). In practice, though that PT systems generally experienced great ridership losses, this trend was not always horizontal among the population groups and local conditions considered.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of travelling by PT during the COVID-19 pandemic is dependent on either the impossibility of using other travel modes, due to economic, social, and housing limitations, or the satisfaction from the quality of delivered services ( Lucchesi et al, 2022 ). In practice, though that PT systems generally experienced great ridership losses, this trend was not always horizontal among the population groups and local conditions considered.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This happened because Public Transport (PT) modes were considered as environments where COVID-19 transmission would be a serious threat due to the relatively small passenger cabin spaces, the often improper functioning of ventilation systems, the inability to identify infected fellow passengers, the vehicles' interior surfaces (e.g., handrails, seats, ticket issuing machines) that are touched by multiple users, the crowded conditions that favour close contact with other people on-board or at stops/stations etc. ( Huang & Li, 2022 ; Kłos-Adamkiewicz & Gutowski, 2022 ; Kumar et al, 2021 ; Lucchesi et al, 2022 ; Monahan & Lamb, 2022 ; Tirachini & Cats, 2020 ). These factors were in turn associated with psychosocial distress among PT users, since their feelings of fear, stress or anxiety increased and their perception of safety, along with their overall travel experience, were accordingly influenced ( Campisi et al, 2022 ; Dong et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“… Lucchesi et al (2022) conducted an online survey of public transportation users in a metropolitan area in southern Brazil and identified the immediate countermeasures which can increase the users' perception of protection while riding public transport. These countermeasures include limiting the number of people in the vehicles, wearing masks, and vehicle hygiene.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To most people though perceptions of safety have probably gotten an extra dimension after COVID-19 was first introduced to our societies. A study from Brazil by Lucchesi and others (2022) showed that crowded vehicles and crowded stops/stations were considered the most detrimental factor in feeling safe while riding in the COVID-19 outbreak. The high number of users in the vehicles and the need to interact with many different people were users’ primary concerns.…”
Section: Literature Reviewmentioning
confidence: 99%